The Paradigm of Education of Idealistic Realism (Commemorating the 115th Anniversary of Professor S. Šalkauskis) - Šernas, Vytautas (Acta Paedagogica Vilnensia, 2002)
Prof. S.Š alkauskis created an original system of pedagogy and philosophical pedagogy synthesizing the concepts of Eastern and Western philosophy, school and society, nation and all-round education of an individual. Combining the concepts of idealism and realism, S. Šalkauskis inspired the birth of philosophical trend in idealistic education, that is, laid the foundations to the paradigm of education of idealistic realism. The main aim of the paradigm is to form an all-round personality, joining different one-sided pedagogical and philosophical trends, educating active creators of culture, civilization, spirituality, society and Lithuanian nation. Idealistic realism as „the world outlook conditioned in its content and aims, directions and individual mind" (S. Šalkauskis) is at the top of the hierarchy of concepts: the general ideal of education; connecting individual nature and civilization - the realistic ideal: the humanist ideal of culture and humanism; the idealistic and pietal ideal of religion and spirituality. The article analyzes the new paradigm of education, its aims and objectives, special terminology, models and typical features, emphasizing synthetical analysis of philosophy, idealism and realism. The new paradigm of education, created on the basis of idealistic realism, demonstrates the undeniable advantages of this paradigm from the aspect of ontology, epistemology, axiology and results. The combination of pragmatical and spiritual aims and objectives allows the flexible formation of not only a specialist and a performer, but also an inspired and unselfish professional. Humanity will eventually destroy itself because of dominating information and knowledge systems, models of knowledge education, proposed by philosopher-realists. Marching into the 21st century, it is necessary to combine realism and idealism, grounding the information-systemic, cultural and spiritual models.